PENGARUH IKLIM ORGANISASI SEKOLAH TERHADAP PRESTASI BELAJAR SISWA DI SMA NEGERI 3 PONTIANAK - Wijaya, Wahyu; Witarsa, Witarsa; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis thesis entitled, "The Effect of School Organizational Climate Against Student Achievement At Sma Negeri 3 Pontianak". The variables in this study consisted of the independent variable (X), the Organizational Climate and the dependent variable (Y), the Learning Achievement. The method used in this research is descriptive research method with a form of research Ex postfakto. The population in this study were all students members of OSIS SMA Negeri 3 Pontianak period 2018/2019. While the sample in this research is all student members of OSIS SMAN 3 Pontianak 2018/2019 period obtained through techniques Saturated samples. The results showed that organizational climate has an influence on student achievement member OSIS SMAN 3 Pontianak period 2018/2019. Based on calculations using SPSS version 24Greater CR = 6.635 t table = 1.753 (CR> t table) and obtained figures correlation coefficient of 0.754, which means there is a positive influence on the school Organizational Climate influence on student learning achievement in SMAN 3 Pontianak. Keywords: Organizational Climate, Learning Achievement